PERFORMANCE E PERFORMATIVIDADE: APROXIMAÇÕES ENTRE JUDITH BUTLER E J. L. AUSTIN - Arbo, Jade Bueno (2021)
For a long time, John Searle has maintained the interpretative monopoly J. L. Austin’s speech act theory, which resulted in a pragmatics that is not capable of encompassing the disruption brought about by Austinian propositions regarding the way we do things with words. Responding to Rajagopalan’s challenge for a socially relevant and socially engaged pragmatics, in this paper we bring together the speech act theory as proposed by J. L. Austin and the concept of gender performativity as presented by Judith Butler, as a way of both establishing a better understanding of the ways in which Butler articulates language in how she understands the subject and exploring a development in speech act theory unforeseen by its original proponent. In order to do so, we briefly review the speech act theory as proposed by Austin; then, we provide a general understanding of Butler’s understanding of gender as performative; finally, we propose a convergence between both philosophers, which are very different from one another, in order to better understand gender as a product of language that acts upon and through individuals, outlining, in a way, the boundaries of social existence. We hope to establish through this theoretical discussion, establish a pathway for thinking pragmatics as a discipline which is always aware and informed by the social developments of language, in order to go beyond descriptivist efforts of canonized interpretations of Austin’s philosophy.